Feline gastrointestinal eosinophilic sclerosing fibroplasia: 13 cases and review of an emerging clinical entity. Issue 5 (May 2015) - Linton, Michael; Nimmo, Judith S; Norris, Jacqueline M; Churcher, Richard; Haynes, Sophia; Zoltowska, Agnieszka; Hughes, Sunishka; Lessels, Naomi S; Wright, Miranda; Malik, Richard
Objective: Feline gastrointestinal eosinophilic sclerosing fibroplasia (FGESF) is a recently described inflammatory disease of cats affecting stomach or intestines and draining regional lymph nodes. This study presents clinical and laboratory data on 13 newly described cases from Australia (11) and the UK (two). Observations: The disease was most often observed in middle-aged cats (median 7 years of age; interquartile range 5–9 years). Ragdolls (7/13) and males (9/13) were overrepresented. Cats generally had a long history of vomiting and/or diarrhoea. Lesions were typically large, hard, non-painful, easily palpable and most commonly situated near the pylorus or ileocaecocolic junction. Lesions were heterogeneous ultrasonographically and on sectioning at celiotomy or necropsy. Masses were hard and 'gritty' on fine-needle aspiration due to internal trabeculae made up of mature collagen bundles. Bacteria were commonly detected within masses (9/13 cases) using either culture or conventional light microscopy and a panel of special stains, and/or fluorescence in situ hybridisation (FISH), although detection often required a diligent search of multiple tissue sections. A consistent bacterial morphology could not be appreciated among the different cases. Outcome: Patients were treated with a variable combination of cytoreduction (debulking and biopsy, to complete surgical resection), immunosuppressive therapy and antimicrobial agents. Many cats had a poor outcome, which was attributable to late diagnosis combined with suboptimal management. It is hoped that suggestions outlined in the discussion may improve clinical outcomes and long-term survival in future cases.